Just so stories for little children - Kipling, Rudyard, 1865-1936 (New York : Weathervane Books, 1865)
Twelve stories about animals, insects, and other subjects include "How the Camel Got His Hump." "The Butterfly That Stamped," and "How the Alphabet Was Made."
How the whale got his throat -- How the camel got his hump -- How the rhinoceros got his skin -- How the leopard got his spots -- The elephant's child -- The sing-song of old man kangaroo -- The beginning of the armadilloes -- How the first letter was written -- How the alphabet was made -- The crab that played with the sea -- The cat that walked by himself -- The butterfly that stamped
Reprint of the 1902 edition published by McMillan, London
Illustrations by the author
Keywords: Children's stories, English